(untitled) (Journal of Bangladesh Academy of Sciences, 2021)
Saint Martin’s Island is a unique coral island in Bangladesh. Locally available fish species (both fresh and dry fish) were collected from the island to study moisture, ash, fat, protein content, fatty acid compositions and heavy metals. Fish oil was extracted from samples by solid phase dispersion method and fatty acid compositions were analyzed by GC-FID. Protein content in fresh fish samples was determined by the micro-Kjeldahl method. Homogenized samples were digested, filtered and analyzed by AAS for determining toxic heavy metals in the fish samples. The fresh fishes appear to be a good source of dietary protein. Journal of Bangladesh Academy of Sciences, Vol. 44, No. 2, 191-195, 2020